Acute effects of cold therapy on knee skin surface temperature: gel pack versus ice bag. Issue 1 (7th December 2015) - Breslin, Matthew; Lam, Patrick; Murrell, George A C
Abstract : Background: To our knowledge there has been no research that has compared the effectiveness of two popular cold therapy modalities applied to healthy human knees, with a surgical dressing, over a 4 h period. Hypothesis: To determine whether gel packs are more effective than ice bags at reducing skin surface temperature in humans. Study design: This was a randomised, repeated measures crossover study, which included nine healthy participants. Level of evidence: Level 2. Methods: Two cold therapy modalities—a gel pack (DonJoy-Orthopaedic Pty Ltd, Normanhurst, New South Wales, Australia) and an ice bag (ICE'N'EASY, Bokarina, Queensland, Australia)—were applied on top of a surgical dressing, covering the knee. Each participant randomly received two cold therapy treatments, in separate sessions, at least 4 days apart. Each session utilised the time protocol of 20 min application on the hour, for 4 h. Skin surface temperature was recorded throughout the session at 1 min intervals. Results: In the first application, the ice bag (5°C±1.7°C) was more effective at reducing skin surface temperature (p<0.04) from baseline than the gel pack (4°C±0.9°C), and had a significantly greater cooling rate (p<0.02). On the subsequent three applications, both modalities were just as effective at reducing skin surface from baseline, and had similar cooling rates. Conclusions: An ice bag initially was more effective than the gel pack at reducing skin surface temperature of healthy knees, with a surgical dressing. Over a 4 h period both gel packs and ice bags were just as effective at reducing skin surface temperature and at maintaining these lower temperatures.